IMPROVING THE ACCOUNTING OF FINANCIAL RESULTS BASED ON INTERNATIONAL STANDARDS: https://doi.org/10.5281/zenodo.15486879 - Obidov , Rakhmonali (Journal of Contemporary World Studies, 2025)
This article is an improvement of accounting for income and expenses, which analyzes the methodology for effective management of the financial activities of an enterprise or organization, accurate and complete calculation of income and expenses. Modern approaches to determining income and expenses, their grouping, calculation methods and their monitoring are considered. In this regard, the issues of modernization, automation, and the use of digital technologies in accounting and audit processes are analyzed with special attention.